Mediated identity construction across cultures : an analysis of reports on the Guguletu Seven - Du Plooy, Daniel Rupert (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (General Linguistics))--University of Stellenbosch, 2008.